The 'market' metaphor and climate change: an epistemological application in the study of green economics. (1st December 2008) - Cojanu, Valentin
The paper proposes a critical discussion of the 'market' mindset that is centred on epistemological concerns relative to its increasing application to matters which predominantly involve moral choices. The issue of climate change is explicitly defined in terms of ethical responsibility to future generations and becomes a natural candidate to discuss the analytical relevance of incorporating the 'market' paradigm into the study of green economics. This investigation gathers factual data based on the search for market solutions in the economics of climate change. The main argument is developed along the representations of the 'market' metaphor in its perfect (market-clearing) and imperfect (market-failure) variants. Both theoretical arguments and observational data seem to offer convincing support to the view that the 'market' mindset plays a controversial role in devising feasible policy recommendations. If climate change can be seen as a global public good, expectations are that the voluntary initiatives to mitigate global warming are to be accompanied by the selfish pursuit of people's own material interest, with the remaining combinations between empathy and self-interest in between.